The 2017 Physics Nobel Prize and the Brazilians Institutions of the Physical Researches - José Maria Filardo Bassalo (Caderno Brasileiro de Ensino de Física, 2018)
In this article, will be addressed the Nobel Prize in Physics of 2017, awarded to American physicists Rainer (“Rai”) Weiss (of German origin), who received half, and the other half was split, by Barry Clark Barish and Kip Stephen Thorne – for the decisive contributions in the construction of the LIGO detector and the observation of gravitational waves – according to the Nobel Committee (CN). We also analyze these waves and their detection, as well we show the relationship between these three nobelists.